2017
DOI: 10.1159/000457832
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil Enhances Quantity of Immature Neurons and Promotes Functional Recovery in the Developing Ischemic Mouse Brain

Abstract: Background: Hypoxic-ischemic (HI) injury to the developing brain occurs in 1 out of 1,000 live births and remains a major cause of significant morbidity and mortality. A large number of survivors suffer from long-term sequelae including seizures and neurological deficits. However, the pathophysiological mechanisms of recovery after HI insult are not clearly understood, and preventive measures or clinical treatments are nonexistent or not sufficiently effective in the clinical setting. Sildenafil as a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
2
7
0
2
Order By: Relevance
“…While this is not exactly the same as the hypoxia occurring during ischemic stroke, it is consistent with previous findings that sildenafil promotes neurogenesis after focal cerebral ischemia [117][118][119]. Engels and collaborators [116] proposed that Sildenafil altered the levels of Wnt signaling pathway members β-catenin and GSK-3, via inhibition of phosphodiesterase type 5, and subsequent increase in cGMP levels. Although they did not find any direct evidence of affected neuroinflammation, GSK-3 and Wnt signaling has been implicated in the regulation of neuroinflammation in several studies [120,121].…”
Section: Drugs Targeting Neuroinflammation To Alter Neurogenesissupporting
confidence: 89%
See 1 more Smart Citation
“…While this is not exactly the same as the hypoxia occurring during ischemic stroke, it is consistent with previous findings that sildenafil promotes neurogenesis after focal cerebral ischemia [117][118][119]. Engels and collaborators [116] proposed that Sildenafil altered the levels of Wnt signaling pathway members β-catenin and GSK-3, via inhibition of phosphodiesterase type 5, and subsequent increase in cGMP levels. Although they did not find any direct evidence of affected neuroinflammation, GSK-3 and Wnt signaling has been implicated in the regulation of neuroinflammation in several studies [120,121].…”
Section: Drugs Targeting Neuroinflammation To Alter Neurogenesissupporting
confidence: 89%
“…Another study reported that the drug Sildenafil promoted neurogenesis and was able to enhance functional recovery after perinatal/pediatric ischemia in mice [116]. While this is not exactly the same as the hypoxia occurring during ischemic stroke, it is consistent with previous findings that sildenafil promotes neurogenesis after focal cerebral ischemia [117][118][119].…”
Section: Drugs Targeting Neuroinflammation To Alter Neurogenesissupporting
confidence: 86%
“…Sildenafil’s potential effects on neonates have been tested using animal models after hypoxia-ischemia. Sildenafil decreased neurological deficits 20 days post-injury as measured by a gait analysis ( Yazdani et al, 2016 ) and promoted motor functional recovery 7 days post-injury as measured by an open-field test ( Charriaut-Marlangue et al, 2014 ) and 30 days post-injury as measured by an elevated plus maze (EPM) and wire hang test ( Engels et al, 2017 ).…”
Section: Effects Of Sildenafil On Brain Functionmentioning
confidence: 99%
“…Otra opción terapéutica sobre la que se han realizado investigaciones es el sildenafilo, un fármaco utilizado en la disfunción eréctil y la hipertensión pulmonar que actúa como inhibidor de la fosfodieterasa 5, evitando de esta forma la hidrólisis del guanosín monofosfato cíclico y favoreciendo la neurogénesis [145]. Se ha apreciado un aumento significativo de la población de neuronas inmaduras en la ZSV ipsilateral a la lesión HI y en el cuerpo estriado de ratones a los que se administró este fármaco.…”
Section: Otras Terapiasunclassified
“…Se ha apreciado un aumento significativo de la población de neuronas inmaduras en la ZSV ipsilateral a la lesión HI y en el cuerpo estriado de ratones a los que se administró este fármaco. Además, tiene la capacidad de mejorar la recuperación funcional [145].…”
Section: Otras Terapiasunclassified